PELATIHAN PEMANFAATAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM LAYANAN ADMINISTRASI AKADEMIK - Ali Idrus; Bradley Setiyadi; Robin Pratama; Ferdiaz Saudagar (Universitas Majalengka, 2023)
In the current era of globalization, it has become a necessity for the use of Information and Communication Technology (ICT) for academic administrative services in schools. The use of ICT for academic administrative services is nothing new in Indonesia. However, there are still many teachers and administrative staff at every school in Indonesia who still do not use ICT for academic administrative services. This can not be separated from the lack of access of teachers and administrative staff to ICT itself. This lack of access may cause teachers and administrative staff in some schools to still use conventional academic service styles, causing strengthening of governance, accountability and public image of school institutions to be less positive. The use of a conventional academic service style, for example a manual student assessment process, if left unchecked may cause a school as a